Implementation of Incinerator Technology for Creative Economy-Based Waste Management in the MARDIKO Scavenger Community, Piyungan, Bantul, Yogyakarta - Sarjito, Sarjito; Magfirona, Alfia; Wiyadi (Universitas Muhammadiyah Surakarta, 2025)
Considering the results of the community service implementation team's observations and investigations, there are three main problems faced by the MARDIKO Scavenger Group in Sitimulyo Piyungan Village, Bantul, Yogyakarta as a PkM partner in pioneering a creative economy-based cooperative. First, lack of knowledge and skills about waste processing that generates additional income. Second, scavengers in their daily lives only look for used goods from waste carried by garbage trucks heading to the disposal area. Third, community awareness and involvement in waste management are still very low, whereas if waste can be recycled, it will produce products that can be additional income for the scavenger group. The PkM implementation method is through the science and technology diffusion method by making and applying an incinerator to process non-organic waste and hazardous substances by burning. The purpose of burning waste is to process waste so that it can reduce its volume and danger, in addition to capturing or destroying hazardous substances that may be released during combustion. In resolving problems in the social, production and marketing fields experienced by the MARDIKO scavenger group, the implementation of the PKM program is carried out through 5 program stages, namely socialization and community awareness, training, application of incinerator technology, utilizing ash from burning for bricks, intensive assistance and evaluation of program sustainability.